Artificial lipid-protein complexes accelerate cholesterol crystallisation in model bile - Hrbasová, M; Vondrusková, R; Spundová, M; Marecek, Z; Entlicher, G (The international journal of biochemistry & cell biology, 2000)
Cholesterol gallstone disease is one of the major health problems in the world. Substances which can affect the crystallisation of cholesterol from human bile have been given considerable attention. Various substances (among them natural lipid-protein complexes) have been tested for cholesterol crystallisation-promoting activity. Various artificial lipid-albumin complexes have been prepared of which taurodeoxycholate-human serum albumin-calcium ions (TDC-HSA-Ca(2+)) had the highest cholesterol crystallisation-promoting activity. This cholesterol crystallisation-promoting activity is similar to that for the lipid-protein complex isolated from native human bile [concanavalin A nonbinding fraction (con A(-) fraction)]. Addition of cholesterol to the TDC-HSA-Ca(2+) complex further increased the cholesterol crystallisation-promoting activity whereas the addition of lecithin had an opposite effect. The interaction of individual components of the TDC-HSA-Ca(2+) complex was followed using several methods. A new effect of Ca(2+) ions (increase in the number of binding sites for bile salts) on the interaction of TDC with HSA was found by equilibrium dialysis. Interaction of TDC with albumin and Ca(2+) did not induce any modification of the secondary structure of albumin. The results of fluorescence spectroscopy may indicate that TDC is at least partially bound to not essentially fatty acid free HSA somehow via admixtures, probably fatty acids. Difference absorption spectrum of the TDC-HSA-Ca(2+)-cholesterol complex was very similar to that of the "natural" lipid-protein complex (con A(-) fraction). From the three drugs with different albumin binding characteristics, only sulphadimethoxin had an observable effect on the cholesterol crystallisation-promoting activity. The action of the TDC-HSA-Ca(2+) complex decreased significantly after the addition of sulphadimethoxin. The addition of TDC modified the absorption spectrum of the sulphadimethoxin-HSA-Ca(2+) complex. It can be suggested that the complex of HSA with bile salts (TDC mainly) and Ca(2+) forms a nucleation centre for cholesterol crystallisation in bile.
Keywords: Crystallization; Calcium; Cholesterol; Bile Acids and Salts; albuminy; lidé; Albumins; cirkulární dichroismus; Taurodeoxycholic Acid; krystalizace; Circular Dichroism; Humans; fluorescenční spektrometrie; žlučové kyseliny a soli; kyselina taurodeoxycholová; Spectrometry, Fluorescence; vápník; cholesterol